Konsep dan Aplikasi IPTEK Nuklir di Sekolah Menengah Atas - Mariati – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
This study aimed to examine the curriculum at the senior secondary school related to nuclear science and technology in content standards, textbooks, teaching methods, and teacher understanding. Locations determined by purposive sampling in six provinces namely Yogyakarta, East Java, West Nusa Tenggara, East Kalimantan, Riau Islands, and South Sulawesi. The respondent are a teachers of Biology, Physics, and Chemistry respectively 18 people in each province. The research method is a survey and focus group discussion. The study shows that nuclear science content standards are adequate, but the application of nuclear science and technology of today need to be added. Textbooks used is more theory and less contextual of life. Nuclear science and technology learning in general lectures, discussions and giving assignments. Teachers’ understanding of the concepts and applications of nuclear science and technology is still low. The study recommends the present applications of nuclear science and technology need to be added to the content standards, schools need to socialize to the understanding of nuclear science and technology is better, should be made in the book supplements or media-based learning model using information and communication technology to support learning of nuclear science and technology for effective, efficient, and fun learning.ABSTRAK Studi ini bertujuan untuk mengkaji kurikulum Sekolah Menengah Atas tentang ilmu pengetahuan dan teknologi nuklir pada standar isi, buku pelajaran, metode pembelajaran, dan pemahaman guru. Sampling kajian ditentukan secara purposif di enam provinsi, yaitu: Daerah Istimewa Yogyakarta; Jawa Timur; Nusa Tenggara Barat, Kalimantan Timur, Kepulauan Riau, dan Sulawesi Selatan. Responden terdiri atas guru Biologi, Fisika, dan Kimia masing-masing 18 orang setiap provinsi. Studi dilakukan melalui survei dan focus group discussion. Hasil studi menunjukkan bahwa iptek nuklir pada Standar Isi cukup memadai, namun dalam aplikasi sangat kurang. Ilmu pengetahuan dan teknologi nuklir dalam buku pelajaran lebih banyak teori dan kurang kontekstual. Pembelajaran iptek nuklir pada umumnya dilakukan dengan metode ceramah, diskusi, dan penugasan. Pemahaman guru tentang konsep dan aplikasi iptek nuklir masih rendah. Studi merekomendasikan aplikasi iptek nuklir masa kini ditambahkan ke dalam Standar Isi, sekolah perlu melakukan sosialisasi agar pemahaman iptek nuklir lebih baik, begitu juga perlu menambah buku suplemen atau model pembelajaran berbasis teknologi informasi dan komunikasi agar pembelajaran iptek nuklir lebih efektif, efisien, dan menyenangkan.